Peculiarities of State Experts Activity on Secret Issues of the State Penitentiary Service of Ukraine - D. Y. Denischuk (Law and Safety)
The study is focused on the protection of state secrets in the State Penitentiary Service of Ukraine (SPS). The subject matter of scientific work is the features of state experts on secret issues, whose activities play a key role in classifying information as a state secret. The paper is aimed at analyzing the impact of numerous reforms of the SPS system on the composition and characteristics of the relevant state experts.